IMPLEMENTASI METODE BRAINSTORMING DALAM MENINGKATKAN KREATIFITAS BERPIKIR DAN KEMAMPUAN KOLABORATIF SISWA MTs AL-ISHLAH PANAMBANGAN - Moh Noerfiadi; Septi Gumiandari (CV. ADIBA AISHA AMIRA, 2025)
The objective of this study is to determine the effect of the brainstorming method on enhancing creative thinking and collaborative skills of students at MTs Al-Ishlah Panambangan. The method used in this research is quantitative with a quasi- experimental approach. The type of data used is quantitative data, and the source of data is primary data. The data analysis technique employed is the independent sample t-test. The results of the study indicate that brainstorming has an effect on the creativity and collaborative abilities of students at MTs Al-Ishlah Panambangan.